Gasification Reaction Characteristics between Biochar and CO2 as well as the Influence on Sintering Process - Min Gan; Wei Lv; Xiaohui Fan; Xuling Chen; Zhiyun Ji; Tao Jiang (Advances in Materials Science and Engineering)
For achieving green production of iron ore sintering, it is significant to substitute biochar, which is a clean and renewable energy, for fossil fuels. In this paper, the gasification reaction between CO2 and biochar was investigated. The results showed the initial temperature and the final temperature of the gasification reaction between biochar and CO2 were lower, while the maximum weight loss rate and the biggest heat absorption value were much higher than those of coke breeze, which indicated gasification reaction between the biochar and CO2 occurred rapidly at lower temperature. The gasification activation energy of biochar was 131.10 kJ/mol, which was lower than that of the coke breeze by 56.26 kJ/mol. Therefore, biochar had a higher reactivity and easily reacted with CO2 to generate CO. As a result, when biochar replaced coke powder at equal heat condition in sintering process, the combustion efficiency of fuel decreased and was disadvantage to the mineralization of iron ores at high temperature. With the increase of substitute proportion, the sinter yield, tumble strength, and productivity were decreased. The proportion of biochar replacing coke breeze should not be higher than 40%. By reducing the heat replacement ratio of biochar, the yield and quality of sinter got improved.